Responsible leadership: What has been its epistemological development? (2018)
The development of Responsible Leaders is one of the big challenges of the Business Schools committed to the fulfillment of the SDG Sustainable Development Goals. This commitment implies understanding the way in which research is conceived around Responsible Leadership. This article analyzes the epistemological paradigms from which research is developed in this field and proposes the use of experimental methodology. © 2018.